Orientasi Dasar Pertimbangan Penyusunan Rencana Pembangunan DKI Jakarta - Sujarto, Djoko; Karyoedi, Mochtarram (Center for Research and Community Services ITB, 1996)
The DKI Jakarta 1985-2005 Spatial Plan faces many challenges and changes in its implementation due to the rapid growth of Jakarta. These changes are characterized by the development of planning paradigm which influences the formulation of the Spatial Plan, and also the Law No. 24/1992 on Spatial Plan. These phenomenon is the basis for the re-orientation in formulating the DKI Jakarta development plan.